N-linoleyltyrosine resisted the growth of non-small cell lung cancer cells via the regulation of CB1 and CB2 involvement of PI3K and ERK pathways - Yan Hu; Yan Hu; Zhe Zhao; Zhe Zhao; Yuan-Ting Liu; Ze-Cheng Xu; Jing-Yi Li; Jing-Yi Li; Zheng-Yu Yang; Rui-Wang; Yun-Qi Yang; Jia-Hui Zhang; et al. (Frontiers Media S.A., 2023)
Background: N-linoleyltyrosine (NITyr), one of the anandamide analogs, exerts activity via the endocannabinoid receptors (CB1 and CB2), which showed anti-tumor effects in various tumors. Therefore, we speculated that NITyr might show anti-non-small cell lung cancer (NSCLC) effects via the CB1 or CB2 receptor. The purpose of the investigation was to reveal the anti-tumor ability of NITyr on A549 cells and its mechanisms.Methods: The viability of A549 cells was measured by MTT assay, and the cell cycle and apoptosis were both examined by flow cytometry; in addition, cell migration was tested by wound healing assay. Apoptosis-related markers were measured by immunofluorescence. The downstream signaling pathways (PI3K, ERK, and JNK) of CB1 or CB2 were examined through Western blotting. The expressions of CB1 and CB2 were detected by immunofluorescence. Finally, the AutoDock software was used to validate the binding affinity between the targets, such as CB1 and CB2, with NITyr.Results: We found that NITyr inhibited cell viability, hindered the cell cycle, resulted in apoptosis, and inhibited migration. The CB1 inhibitor, AM251, and the CB2 inhibitor, AM630, weakened the aforementioned phenomenon. The immunofluorescence assay suggested that NITyr upregulated the expression of CB1 and CB2. Western blot analysis indicated that NITyr upregulated the expression of p-ERK, downregulated the expression of p-PI3K, and did not affect p-JNK expression. In conclusion, NITyr showed a role in inhibiting NSCLC through the activation of CB1 and CB2 receptors involved in PI3K and ERK pathways.